Recurrent and refractory Ewing sarcoma phase I/II trials: current perspective from the Euro-Ewing Consortium - Ribelles, Antonio Juan; Felix, Arthur; Benavent, Nuria; Escrivá-Fernández, Josep; Brahmi, Mehdi; Gaspar, Nathalie; Gatz, Susanne A.; Grünewald, Thomas G. P.; Linder-Stragliotto, Christina; Palmerini, Emanuela; Pantziarka, Pan; Strauss, Sandra; et al. (JCO precision oncology, 2025)
Purpose - Updated analysis of phase I/II trials in recurrent/refractory (R/R) Ewing sarcoma (EwS) over the past 11 years. - Methods - A systematic review was performed to identify phase I/II trials for R/R EwS in three databases (WHO, US National Library of Medicine, and European Clinical Trials Database) and/or published in PubMed/ASCO/European Society for Medical Oncology websites from 2014 to 2024. The search criteria included EwS OR bone sarcoma OR sarcoma AND Phase-I OR Phase-II. Eligibility and data extraction were performed independently by three reviewers, with priority given to trials with EwS specified data. Trials were categorized by therapeutic intervention, including targeted therapies, immunotherapy, chemotherapy, and combined therapies. - Results - One hundred eight trials met inclusion criteria, predominantly academic (70%) and multicenter (81.5%), with significant US and European collaboration. Trial designs were mainly single-arm, with an increase in multiarm trials in the recent years and increased focus on the pediatric population. Trial modalities emphasized targeted therapies with tyrosine kinase, poly-ADP ribose polymerase, EWSR1::FLI1, and cell cycle inhibitors. Immunotherapy with monoclonal antibodies and CAR-T cells as primary agents is also under investigation. The COVID-19 pandemic coincided with a marked reduction in trial initiation in 2020. Among evaluable data, disease control rates averaged 44% and response rates 8%. - Conclusion - This review highlights evolving therapeutic directions in R/R EwS, with increased emphasis on targeted therapies and immunotherapies. Despite pandemic-related delays, trials have progressed in exploring novel targets, including EWSR1::FLI1 oncogenic fusion and DNA repair pathways. These findings underscore ongoing global efforts to address critical unmet needs in EwS treatment, offering a foundation for future trial designs, especially international, randomized phase‐II trials across all age ranges.